Rebuilding Syria The Middle East's Next Power Game? - Dacrema, Eugenio; Talbot, Valeria (Pubblicazioni ISPI, 2019)
Over the last eight years the Syrian conflict has developed into one of the worst humanitarian tragedies of modern times. More than half a million victims, 5 million refugees abroad and 6 million internally displaced: the figures only capture part of Syria's catastrophe. In addition, there is the less quantifiable damage to the country's social fabric.Against this dramatic backdrop, this ISPI Report aims to answer a few crucial questions: how can a country whose society has gone through such traumas and destruction reimagine itself and its future? What conditions would allow those Syrians who were forced to leave their homes to return? And what are the regional and international dynamics and interests that will shape Syria's future? The Report provides the reader with key tools to understand where Syria is headed and what can be done to avoid the worst scenarios.